IMPROVEMENT OF BALANCED NUTRITIONAL KNOWLEDGE AND SKILLS THROUGH THE DEMONSTRATION OF ISI PIRINGKU IN BASIC SCHOOL CHILDREN - Mardiana Mardiana; Hana Yuniarti; Eddy Susanto (JCES (Journal of Character Education Society), 2021)
Abstrak: Pengetahuan merupakan tahap awal dalam perubahan sikap dan perilaku Kurangnya pengetahuan  mengenai gizi akan berdampak pada timbulnya masalah gizi  yaitu kekurangan zat gizi atau bahkan kelebihan zat gizi.  Pemberian pendidikan gizi sebagai gambaran kepada siswa bahwa pentingnya penerapan gizi seimbang dan juga memberi motivasi agar mau  sarapan pagi sebelum ke sekolah dengan mengkonsumsi sayuran hijau, kacang-kacangan, padi-padian dan buah-buahan yang cukup, sehingga makanan yang dikonsumsi cukup beraneka ragam baik  jumlahnya maupun dalam kualitasnya sesuai dengan porsi anjuran pada isi piringku. Tujuan dari kegiatan ini untuk meningkatkan pengetahuan dan ketrampilan siswa mengenai gizi seimbang melalui demonstrasi Isi piringku pada anak SDN 115 Palembang sebanyak 40 orang. Adapaun metode yang digunakan adalah penyuluhan, demonstrasi dan simulasi. Hasil dari kegiatan pengabmas ini menunjukkan bahwa terjadi peningkatan rata-rata pengetahuan siswa sebesar 38,5 point dan sebanyak 40 orang (100%) siswa dapat mengisi isi piringku dengan benar artinya telah terjadi peningkatan keterampilan siswa dalam mengisi isi piringku. Disarankan kepada siswa agar selalu mengonsumsi makanan bergizi seimbang yang sesuai dengan porsi makan isi piringku.Abstract: Knowledge is the initial stage in changing attitudes and behavior. Lack of knowledge about nutrition will have an impact on the emergence of nutritional problems, namely nutritional deficiencies or even excess nutrients. Providing nutrition education as an illustration to students that the importance of implementing balanced nutrition and also motivating them to have breakfast before going to school by consuming enough green vegetables, nuts, grains and fruits, so that the food consumed is quite diverse. the amount and quality according to the recommended portion on the contents of my plate. The purpose of this activity is to increase students' knowledge and skills regarding balanced nutrition through demonstration of the contents of my plate on child of SDN 115 Palembang as many as 40 students. The methods used are counseling, demonstration and simulation. The results of this community service activity showed that there was an increase in the average student's knowledge of 38,5 points and as many as 40 people (100%) students could fill in the contents of my plate correctly, which means that there has been an increase in student skills in filling out the contents of my plate. It is recommended that students always eat a balanced nutritious diet that matches the portion of the meal that is on my plate.